PENGEMBANGAN LEMBAR KERJA SISWA ( LKS ) TEMA LINGKUNGAN SAHABAT KITA DI KELAS V ( LIMA ) SD MUHAMMADIYAH SANGATTA UTARA - Edi Wiyono; P.M Labulan; Muhammad Siddik (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2020)
The ability of teachers to create an atmosphere of learning that is conducive, effective and fun is one part of the professional competence of educators. The use of student worksheets in the teaching and learning process is one of the main choices for a teacher in arousing interest, motivation and stimulation of learning activities. The aim of this research is to produce a Worksheet product for the Themes of the Environment Around Us, the Human Themes and the 5th grade elementary school environment that are suitable for use in the learning process. The type of this research uses research and development methods or commonly referred to as research and development. This study uses the Borg and Gall development research procedure which consists of nine steps namely, gathering initial information, planning, developing initial product formats, initial trials, product revisions, field trials, product revisions, field trials, and final product revisions. The results showed that the Worksheet Product Students Environmental Themes Around Us Sub Themes Human and Environmental grade V SD used had very good eligibility. This finding is supported by field facts where the material expert validation obtained a score of 90.00%, the media expert validation obtained 92.63%, the linguist validation was 92.7%, the student questionnaire assessment on the field test was 92.4%, and the mean score was The average daily test for students increased by 12.50% from 71.96 to 84.46.